The Light Microscopic Study of Age-Associated Changes in Dog Synovial Membrane Cells - Sagiroglu, Ayse Oya (Medwell Online, 2012)
Age associated structural changes in the synovial membrane cells were studied in 24 Kangal hybrid-breed dogs. Dogs were grouped in. 3 age groups young, middle aged and old. Synovial intima were made of 1-2 layered flat and oval intimal cells in the young group dogs and 3-5 to 2-6 multi-layered cubic and polygonal lining cells in the middle aged and the old dogs. Continuous villi were not present in all the age groups and therefore, it was not possible to determine any change in the amounts of villi in different age groups. Subintima changed from areolar, adipose, areola-adipose and fibrous connective cells, from young to old group dogs. Fibroblasts and various connective tissue cells of the young dogs placed in the deep layers of the subintima. Lymphocytes and plasma cells occurred in the environs of blood vessels. Various connective tissue cells concentrated among the collagen fibers and collagen bundles in the vicinity of blood vessels in middle aged group dogs. In the old group dogs, connective tissue cells decreased in subintima and placed among collagen and elastic fibers.
Keywords: Dog synovial membrane; age-associated changes; intimal lining cells; fibroblasts; mast cells; lymphocytes; plasma cells